Effectiveness of Ultrasound Measured Urinary Bladder Wall Thickness as a = Diagnostic and Follow up Tool in Men With Bladder Outlet Obstruction (Bangladesh Journal of Urology, 2020)
Aim: The present study was undertaken with the aim to standardize ultrasound measured urinary bladder wall thickness (UMUBWT) as an additional routine noninvasive test to assess the bladder outflow obstruction (BOO) and to monitor the therapeutic effects of BOO in follow-up after surgical correction of obstruction.Methods: This is an interventional study (pretest-posttest type of clinical trial) conducted between December 2012 to May 2015 where sample size was 55 and sampling technique was purposive. In BOO patient transabdominal sonography was performed using a 7.5 MHz. probe. The thickness of the anterior bladder wall at the midline was measured in both preoperative and postoperative period ( three months after operation) at 3 points approximately 1 cm apart and the average value was recorded.Results: In this study age range was 21-73 years with mean±SD of age was 48.76±15.08 years. In BOO patient preoperative UMUBWT was 0.51 ± 0.16 cm and which reduced to 0.26 ± 0.05 cm three months after surgical correction of obstruction.Conclusion: UMUBWT is a noninvasive, cheap and easily available additional diagnostic tool for detecting BOO as well as it can measure the therapeutic effects in postoperative period.Bangladesh Journal of Urology, Vol. 22, No. 2, July 2019 p.188-193